Analysis of the Scientific Literacy Skills of Prospective Chemistry Teacher Students on Acid-Base Material - Zakiyah, Hayatuz (Jurnal Profesi Guru Indonesia, 2025)
Scientific literacy skills are essential in the chemistry learning process, especially for prospective chemistry teacher students. Scientific literacy is one of the demands in 21st Century learning. The scientific literacy skills of prospective chemistry teacher students analyzed in this study are the knowledge aspect consisting of 3 sub-aspects, namely content, epistemic, and procedural. The purpose of this study was to determine the initial scientific literacy abilities of prospective chemistry teacher students in the knowledge aspect, especially in 3 sub-aspects, namely content, epistemic, and procedural. This study used a quantitative descriptive method. The sample in this study was 40 students of the Chemistry Education study program who were taken using a purposive sampling technique. The research instrument used was a scientific literacy test. The data collection technique used in this study was through a scientific literacy skills test based on the 2015 PISA Framework, which consisted of 15 questions that were tested on students. The scientific literacy test instrument related to the knowledge aspect was divided into 3 aspects, namely content, epistemic, and procedural, each aspect consisting of 5 questions. The chemical material tested in the science literacy test is acid-base material, because this acid-base material is a chemical material that still contains several abstract material concepts. The data analysis technique used in this study used a percentage formula and interpreted the average score of the test results according to the science literacy scoring guidelines. Based on the results of the study, the scientific literacy aspect of the knowledge of prospective chemistry teachers was divided into three parts, namely the content aspect with a medium category with an average score of 17.19%. In the epistemic aspect, the average score was 12.32% with a low category, and the procedural aspect with an average score of 12.65% with a low category.